RESPONSE OF SPRING BARLEY VARIETIES ON DIFFERENT CULTIVATION TECHNOLOGIES IN THE SOUTHERN PART OF THE ROSTOV REGION - L. P. Beltyukov; E. K. Kuvshinova; R. G. Bershansky; I. V. Moiseenko; I. A. Goryainov (Зерновое хозяйство России, 2018)
In the southern part of the Rostov region we studied effect of different cultivation technologies on productivity of spring barley varieties ‘Vikont’ (for forage) and ‘Priazovsky 9’ (for brewing) in heavy loamy carbonate chernozem (black soil). The technologies varied in doses of mineral nutrition and protection during vegetation.The technological effect was studied according to three methods of primary tillage, i.e. plowing, combined tillage and surface tillage. The study showed that these factors influenced a lot on productivity, grain quality and economic profitability. The varieties showed the greatest productivity and better grain quality when cultivated by intensive technologies using plowing as a primary tillage. The article gives the assessment of economic profitability of spring barley. The improvement of the variety productivity and an increase of intensive cultivation showed economic efficiency reduce. The receiving of the yield per unit area using intensive technologies with a plowing turned to be the most expensive one with a total expenditure of 13287-13386 rub/ha, a prime cost of 3264-3524 rub/ha and a net income of 6173-7114 rub/ha. The cultivation of barley using extensive technologies with a surface tillage turned to be low-cost (6563-6574 rub/ha). The prime cost was the lowest one (2206-2369 rub/ha) and the net income was the highest one (7287-8326 rub/ha). Among all cultivation technologies an extensive method showed the maximum profitability of 95,1-126,7 %,when an intensive method showed only 43,0-53,1%.